2020
DOI: 10.1007/s00127-020-01924-7
|View full text |Cite
|
Sign up to set email alerts
|

Early impacts of the COVID-19 pandemic on mental health care and on people with mental health conditions: framework synthesis of international experiences and responses

Abstract: Purpose The COVID-19 pandemic has many potential impacts on people with mental health conditions and on mental health care, including direct consequences of infection, effects of infection control measures and subsequent societal changes. We aimed to map early impacts of the pandemic on people with pre-existing mental health conditions and services they use, and to identify individual and service-level strategies adopted to manage these. Methods We searched for relevant material in the public domain published … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
169
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 192 publications
(186 citation statements)
references
References 26 publications
13
169
0
4
Order By: Relevance
“…The lead developer of the questionnaire, SJ, an academic and practising inner London psychiatrist, read key sources identified in an accompanying rapid review of relevant literature [13], including academic and professional journals, news media, and organisational websites, and followed relevant social media topics. The drafting of the questionnaire was further informed by the NIHR Mental Health Policy Research Unit (PRU) working group for this study (about 30 people, including clinicians, researchers, and people with relevant lived experience), and the PRU Lived Experience Working Group.…”
Section: Questionnaire: Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The lead developer of the questionnaire, SJ, an academic and practising inner London psychiatrist, read key sources identified in an accompanying rapid review of relevant literature [13], including academic and professional journals, news media, and organisational websites, and followed relevant social media topics. The drafting of the questionnaire was further informed by the NIHR Mental Health Policy Research Unit (PRU) working group for this study (about 30 people, including clinicians, researchers, and people with relevant lived experience), and the PRU Lived Experience Working Group.…”
Section: Questionnaire: Developmentmentioning
confidence: 99%
“…Our questionnaire was by necessity an ad hoc and not an established and validated tool. Omissions were noted as the study progressed: it was assumed that impacts of the "lockdown" for service users were negative, but positive experiences are noted too, for example of reduced pressure or easier access for people who struggle to travel [13]. More importantly, we designed the questionnaire early in the pandemic when the evidence of differential effects on some ethnic groups was less striking [19]: closed questions do not focus on this, although these effects and issues of racism are included in open-ended responses on concerns for the future.…”
Section: Limitationsmentioning
confidence: 99%
“…In a few weeks, COVID-19 had a significant impact on worldwide economies, social, cultural and organizational entities, as well as on individuals' mental and physical health, reaching the level of crisis as defined by the World Health Organization, i.e., an insidious process that cannot be defined in time 1 . The several lockdowns adopted by most countries were shown to have detrimental effects, including posttraumatic stress symptoms, confusion, or anger; some of these are long lasting effects 2 , which demonstrates the negative impact of COVID-19 on mental health [3][4][5][6] . Additionally, women, young people, and people who lost their job, reported the most severe psychological J o u r n a l P r e -p r o o f Covid-19 and sexual health symptoms 7 .…”
Section: Introductionmentioning
confidence: 99%
“…1 A more recent international review found multiple reports that the pandemic aggravated symptoms for those who previously struggled with their mental health. 2 One can see the increase in symptoms by looking at the statistics surrounding requests for mental health resources. In the early weeks of the pandemic in the United States, the National Alliance on Mental Illness saw calls and e-mails to its helpline leap 40%.…”
mentioning
confidence: 99%